Completely multiplicative functions arising from simple operations - Vichian Laohakosol; Nittiya Pabhapote (International Journal of Mathematics and Mathematical Sciences)
Given two multiplicative arithmetic functions, various conditions for their convolution, powers, and logarithms to be completely multiplicative, based on values at the primes, are derived together with their applications.